Special Issue: The Role of Microorganisms in the Evolution of Animals and Plants - Eugene Rosenberg; Ilana Zilber-Rosenberg (Microorganisms, 2022)
It is now well established that all animals and plants harbor abundant and diverse microorganisms, including bacteria, archaea, viruses, and eukaryotic microorganisms [...]